1979
DOI: 10.1002/zamm.19790591004
|View full text |Cite
|
Sign up to set email alerts
|

Creep Transition in Thick‐Walled Cylinder under Internal Pressure

Abstract: Transitional stresses for thick‐walled cylinder under internal pressure for the three stages of creep has been derived. For stationary stage of creep, the stresses and the assumed stress‐strain rate relations are the same as those given by Bailey, Odquist and others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…In order to calculate the creep stresses, we define the transition function R = ( − ) through the principal stress difference as taken by Seth, Hulsarkar, Gupta [4,5,7].…”
Section: Solution Through Principal Stress Differencementioning
confidence: 99%
“…In order to calculate the creep stresses, we define the transition function R = ( − ) through the principal stress difference as taken by Seth, Hulsarkar, Gupta [4,5,7].…”
Section: Solution Through Principal Stress Differencementioning
confidence: 99%
“…It has been shown that the asymptotic solution through the principal stress [11][12][13][14][15][16][17][18][19][20][21][22][23] leads from elastic to plastic state at the transition point P → ±∞ . If the transition function R is defined as:…”
Section: Solution Through Problemmentioning
confidence: 99%
“…This theory [10] does not required any assumptions like an yield condition, incompressibility condition and thus poses and solves a more general problem from which cases pertaining to the above assumptions can be worked out. It utilizes the concept of generalized strain measure and asymptotic solution at critical points or turning points of the differential equations defining the deformed field and has been successfully applied to a large number of problems [11][12][13][14][15][16]. SETH [10] has defined the generalized principal strain measure as:…”
Section: Introductionmentioning
confidence: 99%
“…hydraulic cylinders, gun barrels, pipes, boilers and fuel tanks), accumulator shells, cylinders for aerospace and military applications, pressure vessels for transportation of industrial gases or highly pressurized fluids and piping of nuclear reactors (Arya and Bhatnagar, 1976;Perry and Aboudi, 2003;Becht and Chen, 2000;Bhatnagar et al, 1980). In some of these applications, the cylinder is exposed to high temperature along with severe mechanical loadings, thus leading to significant creep and reduced it's the useful service life (Gupta and Pathak, 2001;Hagihara and Miyazaki, 2008;Tachibana and Iyoku, 2004). The excellent mechanical properties, such as high specific strength and stiffness, and high-temperature stability, offered by aluminum/aluminum alloy-based composites consisting of silicon carbide (SiC) particles (SiC p ), whiskers or fibers make them suitable for use in cylindrical components subjected to severe thermo-mechanical loadings (Gupta et al, 2005).…”
Section: Introductionmentioning
confidence: 99%